Massacre pond - Doiron, Paul (Doiron, Paul. Mike Bowditch mysteries, 2014)
Investigating the senseless slaughter of five moose found on the estate of a wealthy animal rights activist, game warden Mike Bowditch finds the controversial case turning more sinister when the activist's daughter is killed in a suspicious accident.